PENGEMBANGAN KETERAMPILAN PROSES SAINS SISWA KELAS V PADA MATERI GAYA GESEK MELALUI PEMBELAJARAN KONTEKSTUAL - Gusdiantini, Lela; Aeni, Ani Nur; Jayadinata, Asep Kurnia (Jurnal Pena Ilmiah, 2017)
This research tilte is "Development of Science Skills of Grade V Student on Material Friction Through Contextual Learning". Result of research with significance level a = 0,05 shows first, there is improvement of process skill of student loe group after using contextual approach. Secondly, there is an increase in the science process skill of the group students using contextual approach. Third, there is an increase in the science process skills of high group students after applied contextual approach. Fourthly, there is an enhancement of superior group science process skills using a contextual approach. Fourthly, there is a difference in the improvement of science process skills in the students of the low group, medium group, and high groups as evidenced by the difference test results of the average gain of the three groups with Asymp values. Sig. 0,000. Fifth.